Relationships Among Fatigue, Anxiety, Depression, and Pain and Health-Promoting Lifestyle Behaviors in Women With Early-Stage Breast Cancer. Issue 2 (March 2020) - Kelly, Debra Lynch; Yang, Gee Su; Starkweather, Angela R.; Siangphoe, Uma; Alexander-Delpech, Paula; Lyon, Debra E.
Abstract : Background: With a nearly 89% 5-year survival rate for women with early-stage breast cancer, symptoms are a priority. Healthy lifestyle behaviors may be temporally associated with symptoms; however, evidence is lacking. Objective: This research examined temporal relationships among healthy lifestyle behaviors and symptoms in women diagnosed with breast cancer receiving chemotherapy. Methods: This research was part of a study (R01NR012667) approved by the institutional review board. Women (n = 76) providing written informed consent participated in this longitudinal study examining health-promoting lifestyle behaviors and symptoms (fatigue, anxiety, depression, and pain). Participants completed well-validated self-report questionnaires primarily at a clinic visit. Statistical methods included descriptive statistics, linear mixed-effects models, and pairwise comparisons using SAS 9.4; α was set at .05. Results: Lowest healthy lifestyle behavior scores for physical activity and highest scores for spiritual growth were reported. Significant changes in physical activity and stress management were noted. Fatigued patients had lower physical activity and nutrition scores than did patients without fatigue. Patients with anxiety had lower spiritual growth and interpersonal relation scores than did patients without anxiety. Relationships demonstrated temporal differences. Conclusions: Breast cancer survivors did not routinely engage in healthy lifestyle behaviors. Significant temporal changes in healthy lifestyle behaviors and symptoms and significant associations among healthy lifestyle behaviors, symptoms, and demographic and clinical factors were noted in this study. Implications for Practice: Knowing the temporal relationships among these variables provides insight that could be useful for nurses so they can encourage healthy lifestyle behaviors to mitigate symptoms throughout the cancer trajectory.